Passive immunity in newborn from SARS‐CoV‐2‐infected mother. Issue 3 (10th November 2020) - Cavaliere, Anna F.; Marchi, Laura; Aquilini, Donatella; Brunelli, Tamara; Vasarri, Pier L.
Abstract: Severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) vertical transmission is an open issue. Recent reports call into question in utero or peripartum viral transmission to the offspring. Few data are available on immunoglobulin G (IgG) and/or IgM in newborns. Insufficient evidence is available regarding passive immunity in neonates born from SARS‐CoV‐2 infected women. We report a case of a neonate showing the presence of blood specific IgG and the absence of IgM and negative nasopharyngeal swab. He was born from an asymptomatic SARS‐CoV‐2‐infected mother with positive IgG and IgM. The transplacental passage of specific IgG antibodies from the affected mother to the unaffected fetus highlights neonatal passive immunity. Highlights: The risk of vertical transmission of SARS‐CoV‐2 is still an open question. In affected SARS‐CoV‐2 pregnant women, investigation of vertical transmission and passive immunity requires the detection of the virus in the placenta, amniotic fluid and newborn and both the maternal and neonatal IgG and IgM. Passive immunity may offer temporary protection to the newborn. Studies are needed to determine the duration of this protection.